Kerangka Adaptasi Pada Optimasi Pendapatan Industri Mebel Skala Usaha Kecil dan Rumah Tangga di Kota Kupang - Laurentius Desy Wisnu Wardhana; Apolonia Febronia Djuita; Luisa Moi Manek; Fabianus Ranta; Adrin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
The limitations of production optimization approaches in small-scale and household furniture industries generally fail to account for parameter stability under conditions of market uncertainty. Although linear programming (LP) has been widely applied to microenterprises in Indonesia, most studies focus solely on optimal solutions without examining parametric stability, thereby creating a research gap. This study was conducted in Kupang City, East Nusa Tenggara, using primary data from 72 business units. Two LP models based on the simplex method were formulated and analyzed using sensitivity and demand scenario approaches. The results indicate that the optimal solution is sensitive to changes in profit coefficients, particularly for doors and cabinets, which have a narrow stability range. Skilled labor is the primary constraint, while capital and raw materials are unconstrained. Scenario analysis indicates potential revenue fluctuations, necessitating a scenario-based adaptation framework to support evidence-based decision-making.